Dual blockade of angiotensin‐II and aldosterone suppresses the progression of a non‐diabetic rat model of steatohepatitis. Issue 7 (20th November 2012) - Noguchi, Ryuichi; Yoshiji, Hitoshi; Ikenaka, Yasuhide; Kaji, Kosuke; Aihara, Yosuke; Shirai, Yusaku; Namisaki, Tadashi; Kitade, Mitsuteru; Douhara, Akitoshi; Moriya, Kei; Fukui, Hiroshi
<x xml:space="preserve">Abstract</x> Aim Both angiotensin‐II (AT‐II) and aldosterone (Ald) play pivotal roles in the pathogenesis of diseases in several organs including the liver. We previously reported that suppression of AT‐II and Ald with angiotensin‐converting enzyme inhibitor (ACE‐I) and selective Ald blocker (SAB), respectively, attenuated the rat liver fibrogenesis and hepatocarcinogenesis. The aim of our current study was to elucidate the combined effects of ACE‐I and SAB in the progression of a non‐diabetic rat model of steatohepatitis, and the possible mechanisms involved. Methods In the choline‐deficient L‐amino acid‐defined (CDAA) diet‐induced model, the effects of ACE‐I and SAB on liver fibrosis development and hepatocarcinogenesis were elucidated, especially in conjunction with neovascularization. Results Treatment with both ACE‐I and SAB suppressed the development of liver fibrosis and glutathione‐S‐transferase placental form (GST‐P) positive pre‐neoplastic lesions. The combined treatment with both agents exerted more inhibitory effects as compared with either a single agent along with suppression of the activated hepatic stellate cells (Ac‐HSC) and neovascularization, both of which play important roles in these processes. Our in vitro study showed that AT‐II type 1 receptor blocker (ARB) and SAB inhibited Ac‐HSC proliferation and in vitro angiogenesis along with suppression of the in vivo studies. Conclusion Dual blockade of AT‐II and Ald suppresses the progression of a non‐diabetic rat model of steatohepatitis. Because both agents are widely and safely used in clinical practice, this combination therapy could be an effective new strategy against steatohepatitis in the future.